Canine and Human Sesamoid Disease - Cake, M. A.; Read, R. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Sesamoid disease is an important cause of lameness in young, large breed dogs, primarily Rottweilers. The patho genesis of the condition is unknown, although trauma does not appear to be the primary cause. Histological findings of bone necrosis suggest that vascular compromise may be involved. Canine sesamoid disease may therefore be related to idiopathic osteonecrosis of the human hallux sesamoids.
Keywords: Sesamoid disease; dog; osteonecrosis; hallux sesamoids